Testing the mate-choice hypothesis of the female orgasm: disentangling traits and behaviours - Sherlock, James M. (Socioaffect Neurosci Psychol, 2016)
BACKGROUND: The evolution of the female orgasm in humans and its role in romantic relationships is poorly understood. Whereas the male orgasm is inherently linked to reproduction, the female orgasm is not linked to obvious reproductive or survival benefits. It also occurs less consistently during penetrative sex than does the male orgasm. Mate-choice hypotheses posit that the wide variation in female orgasm frequency reflects a discriminatory mechanism designed to select high-quality mates. OBJECTIVE: We aimed to determine (1) whether women report that their orgasm frequency varies between partners, (2) whether this variation reflects mates' personal characteristics, and (3) whether this variation reflects own and partner sexual behaviour during intercourse. DESIGN: We collected survey data from 103 women who rated (1) the extent to which their orgasm frequency varied between partners, (2) the characteristics of previous sexual partners who induced high-orgasm frequency and those who induced low-orgasm frequency, and (3) the specific behaviours during sex with those partners. This is the first study to test within-woman variation in orgasm and partner traits. RESULTS: Overall, women reported variation in their orgasm rates with different partners. Partners who induced high-orgasm rates were rated as more humorous, creative, warm, faithful, and better smelling than partners who induced low-orgasm rates, and also engaged in greater efforts to induce partner orgasm. CONCLUSIONS: Some assumptions and predictions of mate-choice hypotheses of female orgasm were supported, while other aspects of our findings provide reasons to remain sceptical.